To solve the system of equations
- \( 6x - 3y = 18 \)
- \( -3x - 9y = -93 \)
using the elimination/combination method, Emma should aim to eliminate one of the variables. Let's analyze the equations:
The first equation can be simplified by dividing everything by 3:
- \( 2x - y = 6 \) (let's call this Equation 1)
Now, for the second equation, if we multiply it by 1 (keeping it the same), we have:
- \( -3x - 9y = -93 \)
To simplify the second equation, we can divide everything by -3:
- \( x + 3y = 31 \) (let's call this Equation 2)
Now we have the system of equations:
- \( 2x - y = 6 \)
- \( x + 3y = 31 \)
To eliminate one variable, let's consider the possibilities listed in the options:
A. Multiply the first by 3: This would give \( 18x - 9y = 54 \). B. Multiply the first by -2: This would give \( -12x + 6y = -12 \). C. Multiply the second by 2: This would give \( 2x + 6y = 62 \). D. Multiply the second by -3: This would give \( 9x + 27y = 279 \).
Among these options, multiplying the first equation by -2 (Option B) or the second equation by -3 (Option D) would allow us to cancel terms when we add the two equations together. However, multiplying the first equation by -2 is a useful approach because it will directly align the coefficients for elimination with \( y \) terms.
Therefore, the best choice to enable elimination directly would be:
B. multiply the first equation by -2.